-3(2s-4)-12=-2(75+1)-3

Simple and best practice solution for -3(2s-4)-12=-2(75+1)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2s-4)-12=-2(75+1)-3 equation:


Simplifying
-3(2s + -4) + -12 = -2(75 + 1) + -3

Reorder the terms:
-3(-4 + 2s) + -12 = -2(75 + 1) + -3
(-4 * -3 + 2s * -3) + -12 = -2(75 + 1) + -3
(12 + -6s) + -12 = -2(75 + 1) + -3

Reorder the terms:
12 + -12 + -6s = -2(75 + 1) + -3

Combine like terms: 12 + -12 = 0
0 + -6s = -2(75 + 1) + -3
-6s = -2(75 + 1) + -3

Combine like terms: 75 + 1 = 76
-6s = -2(76) + -3

Multiply -2 * 76
-6s = -152 + -3

Combine like terms: -152 + -3 = -155
-6s = -155

Solving
-6s = -155

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Divide each side by '-6'.
s = 25.83333333

Simplifying
s = 25.83333333

See similar equations:

| e^3x=17 | | 15+7a=99 | | 120/((30-29)*5) | | (20/2)*3=30 | | x-2.18=2.24 | | 2g(g+6)=0 | | 3*sin(2*x)=-2 | | -6(-2.8)-28=4(-2.8) | | 2v/2(v-2)-7(v-2) | | -6(2.8)-28=4(2.8) | | 4.9/10 | | 7np-2p-5+(np+p-4)= | | V=R-1 | | 19x-38=0 | | 24x-80=12x-100 | | 2y+25=2y-30 | | -4x+3(-6x-16)=18 | | V=1R | | 14bg-5bg-8bg= | | 2x=(x-2)+4 | | log(x+5)13=1 | | V=1timesr | | 19=-x-9 | | 6x-21=87 | | 15x+35=8x-70 | | 21x+70=-140 | | 125^3b=1/25 | | 20-3w=10+4w | | 8a-6=3a+4 | | 20=h-1 | | -4(-6w+v)-6(-6v+w)= | | -1(-8.3+2.3)= |

Equations solver categories